Values-Based Scenarios of Water Security: Rights to Water, Rights of Waters, and Commercial Water Rights. (15th September 2021) - Jenkins, Willis; Rosa, Lorenzo; Schmidt, Jeremy; Band, Lawrence; Beltran-Peña, Areidy; Clarens, Andres; Doney, Scott; Emanuel, Ryan E; Glassie, Alison; Quinn, Julianne; Rulli, Maria Cristina; Shobe, William; et al.
Abstract: Although a wide body of scholarly research recognizes multiple kinds of values for water, water security assessments typically employ just some of them. In the present article, we integrate value scenarios into a planetary water security model to incorporate multiple water-related social values and illustrate trade-offs among them. Specifically, we incorporate cultural values for environmental flows needed to sustain ecosystem function (rights of waters), the water requirements of a human right to food (rights to water), and the economic value of water to commercial enterprise (commercial water rights). Pairing quantitative hydrological modeling with qualitative systems of valuing, we suggest how to depict the available water for realizing various combinations of the values underlying those rights. We account for population growth and dietary choices associated with different socioeconomic pathways. This pluralist approach incorporates multiple kinds of values into a water security framework, to better recognize and work with diversity in cultural valuation of water.